Mukjizat bilangan dalam al-Quran: Kajian perbandingan antara Bassam Nihad Jarrar dan ‘Abd al-Da’im al-Kahil / Abu Zaki Ismail - Abu Zaki, Ismail (2017)
Numerical inimitability is an extension of I‘jāz al-Qur’ān theory which has been observed by researchers from various aspects. It is the result of tadabbur of Quran since it has been guaranteed that Quran is protected from all falsehood. The objective of this study is to identify the origin of the numerical study and the concept of numerical inimitability, to study biography of the main researchers, their works and methodology used and also to develop objective standards for numerical inimitability researches. It focused on the history of theory emergence and two researchers who wrote most on numerical inimitability of Quran who were Bassam Nihād Jarrār and ‘Abd al-Da’im al-Kaḥil. Their works involved with the issues of gematria, soothsaying and use of matrix. The study of the origin was indispensable to review allegations and the concept of numerical miracle was influenced by deviant sects or other religions doctrine on worshiping sacred numbers and the use of gematria. This qualitative research used several methods including inductive, deductive, comparative and historiography. Inductive method used in analyzing factors on the rejection of the numerical miracles theory, defining objective standards and making conclusions. Deductive method was used to determine which works were included in the category of numerical inimitability in the literature review and the work lists, and determine which works suit public reading. Methods of comparison between Bassam and ‘Abd al-Da’im involved with their educational background, analysis of their works, topics discussed, calculation methods and sources of their studies. The study found that the theory of Quran numerical inimitability extended to the numerical aspects as the result of the mushaf development and numbering. The numerical studies thrive in the 19th century when human started the use of numbers in life and computers in calculation. Bassam and ‘Abd al-Da’im had contributed a lot of literary works in the study of Quran numerical inimitability. The use of gematria by Bassam was not an issue as it was actually a neutral number system, but using it for soothsaying should be avoided. The use of matrix by ‘Abd al-Da’im generated many discoveries, but he did not meet the basic standards since he counted the waw al-‘atf as a single word that stands on its own. Thus, further studies on numerical inimitability must comply with the standards and its presentation should be simplified so that the idea of Quran numerical inimitability will meet the concept of “the everlasting miracle of the Quran.” The objective and more concise standards to analyse and acknowledge numerical inimitability works was highlighted at the end of the study. In fact,improvement was still needed in this study as it is natural for all new things. It is the sunnah described in the Quran itself. Truly, the inimitability of the Quran will be fully understood by those who observe and specialise in areas related to the Quran miracles aspects.